2018
DOI: 10.1186/s12916-017-0996-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic morbidity, deprivation and primary medical care spending in England in 2015-16: a cross-sectional spatial analysis

Abstract: BackgroundPrimary care provides the foundation for most modern health-care systems, and in the interests of equity, it should be resourced according to local need. We aimed to describe spatially the burden of chronic conditions and primary medical care funding in England at a low geographical level, and to measure how much variation in funding is explained by chronic condition prevalence and other patient and regional factors.MethodsWe used multiple administrative data sets including chronic condition prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Access to health services in London might also be a factor, with some evidence that health services in the north east and north west of England are relatively underfunded compared with London. 41 The low mortality could be, at least partly, related to inaccurate population estimates for London as a consequence of high population turnover from high internal and international migration. Finally, IMD scores might function differently in London; for example, the housing deprivation domain includes a measure of housing affordability, for which London does particularly badly.…”
Section: Discussionmentioning
confidence: 99%
“…Access to health services in London might also be a factor, with some evidence that health services in the north east and north west of England are relatively underfunded compared with London. 41 The low mortality could be, at least partly, related to inaccurate population estimates for London as a consequence of high population turnover from high internal and international migration. Finally, IMD scores might function differently in London; for example, the housing deprivation domain includes a measure of housing affordability, for which London does particularly badly.…”
Section: Discussionmentioning
confidence: 99%
“…The shortcomings of the Carr-Hill formula (see Box 1) to adequately adjust for population need related to deprivation is well recognised. 32,33,34 At practice level, an analysis of payments over time has found that for each 10% increase in deprivation score, practice payments increased by 0.06%. 35 Analysis of consultation rates from the London borough of Tower Hamlets estimated that a formula that allowed for additional workload in deprived areas would equate to 33% more funding for these practices.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that a review is needed, and should consider funding for PCNs (PCNs in deprived areas currently do not get extra funding to account for the likely increased needs of their populations 25 ) and also the underlying resource allocation formula (Carr-Hill). Previous research suggests that the Carr-Hill formula may under-weight for the increased health needs associated with deprivation, 32,33,34 and there is a case for further analysis of the impact of the formula across general practice in England.…”
Section: Considerations For Policymentioning
confidence: 99%
“…In this context, the higher pay per patient in general practices serving rural areas may be relevant. 40 …”
Section: Discussionmentioning
confidence: 99%